THINGS TO CONSIDER IN BLENDED LEARNING CONTEXT: STUDENTS VOCABULARY LEARNING STRATEGIES - Wulandari, Gesia Afifah Ayu; Faliyanti, Eva; Siagiyanto, Bambang Eko; Baihaqi, Yasmika (Premise: Journal of English Education and Applied Linguistics, 2023)
The move from teacher-centered to learner-centered pedagogy, which empowered students to take charge of their learning, has attracted the researcher to conduct this study. This paper explored the types of vocabulary learning strategies (VLSs) used by intermediate learners of English as a foreign language in Lampung universities and the relationship between VLSs and their speaking ability. It also attempted to find out the most-used and least-used strategies for learning the vocabulary of the English language. It adopted a quantitative correlational research design. One hundred seventy-nine participants as intermediate learners from nine different universities in Lampung participated in this study. An adopted 50-item questionnaire of vocabulary learning strategies was used for data collection. This questionnaire was distributed in two separate sessions: online via the Google Form link and offline through a printed questionnaire. The descriptive statistics analysis of the questionnaire's responses showed that the participants were medium strategy users (mean=3,11). Determination and memory strategies were the most frequently used, while social was the least used. Pearson correlation coefficient on SPSS revealed a fragile relationship between VLSs and the participants' speaking ability where the value is r< 0,30 (r= 0,089). Finally, it is recommended that the teachers help their students become initiative and take responsibility for their success by providing them with a sense of vocabulary learning strategies to enhance their vocabulary knowledge. Moreover, teachers should present a wide range of (VLSs) to their students for both a classroom-related setting and self-directed vocabulary learning.